1929
DOI: 10.1021/ie50237a019
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts for the Formation of Alcohols from carbon Monoxide and Hydrogen

Abstract: Experiments on the decomposition of methanol in the presence of catalysts composed of the oxides of zinc and chromium show that an excess of chromium oxide gives rise to reactions producing appreciable amounts of carbon dioxide and unsaturated hydrocarbons. With catalysts containing excess zinc oxide the main products are carbon monoxide and hydrogen, a sharp maximum in activity occurring at a catalyst composition of about Zn7SCr22. The relatively constant percentage of formaldehyde indicates its intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1930
1930
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In the early investigation on methanol synthesis over ZnO/Cr 2 O 3 catalysts prepared by coprecipitation followed by calcination, the synergy observed between ZnO and Cr 2 O 3 in comparison to the pure component oxides was mainly ascribed to an increase in the specific surface area . In addition, ZnO had been generally identified as the only active component, and the promoting role of Cr 2 O 3 was attributed to spinel formation, which prevented the sintering of small ZnO crystallites by providing a considerably larger surface area and better distribution of ZnO particles .…”
Section: Introductionmentioning
confidence: 99%
“…In the early investigation on methanol synthesis over ZnO/Cr 2 O 3 catalysts prepared by coprecipitation followed by calcination, the synergy observed between ZnO and Cr 2 O 3 in comparison to the pure component oxides was mainly ascribed to an increase in the specific surface area . In addition, ZnO had been generally identified as the only active component, and the promoting role of Cr 2 O 3 was attributed to spinel formation, which prevented the sintering of small ZnO crystallites by providing a considerably larger surface area and better distribution of ZnO particles .…”
Section: Introductionmentioning
confidence: 99%
“…Much more active copper-based catalysts were studied and described in the 1920s and 1930s [4][5][6][7][8][9]. These early studies identified copper as a very active metal * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Tab 8. Qualities of methanol product International methanol producers and consumers association.13.13.8.12 Concepts Circumventing the Equilibrium Limitations…”
mentioning
confidence: 99%
“…(8) Franz and Lutze, Ber., 67B, 768 (1924). (9) Griswold, University of Illinois thesis, 1928. (10) I. G. Farbenindustrie, French Patent 662,968 (1928).…”
mentioning
confidence: 99%